PEMAHAMAN TENTANG SABAT LUNAR BERDASARKAN IMAMAT 23:3 DI GMAHK MOUNTAIN VIEW CHURCH KOTA BELUD SABAH MALAYSIA - Benedict Bin Sisom; Alvyn C. Hendriks (Fakultas Filsafat Universitas Advent Indonesia, 2018)
In this research, the author tries to examine the understanding of the Lunar Sabbathbased on Leviticus 23: 3 in Mountain View Church Kota Belud Sabah, Malaysia.Simply, this researchconsisted of four indicators: What is the understanding of theLunar Sabbath according to the Bible in Leviticus 23:3; What is the Sabbath dayaccording to the Sabbath Lunar adherents with itsconnectionto the Sabbath onSaturday; What is the understanding of the Jehovah’s calendar; andhow does theunderstanding of the churches about the Lunar Sabbath?This research is divided intotwo main parts such as theoretically and practically.Theresult of thistheory is,regarding to the understanding of the Lunar Sabbath, we have no Biblical basis tocelebrate the Lunar Sabbath,and the sanctification of the Sabbath is an imperativebiblical doctrine for every people who believes that God is the Creator and theRedeemer. The Sabbath day according to the SabbathLunar adherents with itsconnection to the seventh-day Sabbath is,the Lunar Sabbath adherents claim that thelunisolar calendar is the original biblical calendar in which the Sabbath falls on the8th, 15th, 22nd, and the 29th that falls on Tuesday.The Lord Himself sanctified theSabbath on Saturday in the week of creation.The understanding the Jehovah’scalendaris Jesus crucified on the passoveron the sixth day of the week on 14thandrested on 15thand rose on 16th.But if the Sabbath always falls on that date, surely Godwill not lowered the manna on the 15th (Joshua 5: 10-12) because it is the Sabbath,but according to Joshua 5:10-12,God lowered the manna on the 15th. So the 15th datecannot be a Sabbath.The theory of the Lunar Sabbath and the theory of the Sabbath isSaturday is,for the Lunar Sabbath theory,that on Monday, Tuesday, and Wednesdayit was the day when Jesus was crucified. But according to the Bible, Friday,Saturday, and Sunday are the days of the crucifixion of Jesus.Pratically, thisresearchresult of the respondents provided evidence that all the statements contained in thequestionnaire (P1-P19) are well understood except for P13 to P18 and P19 with poorinterpretation.